General search for supersymmetric particles in scenarios with compressed mass spectra using proton-proton collisions at s = 13 TeV - Chekhovsky,V; Hayrapetyan,A; Makarenko,V; Tumasyan,A; Adam,W; Andrejkovic,JW; Benato,L; Bergauer,T; Damanakis,K; Dragicevic,M; Giordano,C; Hussain,PS; et al. (Physical Review D, 2025)
A general search is presented for supersymmetric particles (sparticles) in scenarios featuring compressed mass spectra using proton-proton collisions at a center-of-mass energy of 13 TeV, recorded with the CMS detector at the LHC. The analyzed data sample corresponds to an integrated luminosity of <a:math xmlns:a="http://www.w3.org/1998/Math/MathML" display="inline"> <a:mn>138</a:mn> <a:mtext> </a:mtext> <a:mtext> </a:mtext> <a:msup> <a:mi>fb</a:mi> <a:mrow> <a:mo>−</a:mo> <a:mn>1</a:mn> </a:mrow> </a:msup> </a:math> . A wide range of potential sparticle signatures are targeted, including pair production of electroweakinos, sleptons, and top squarks. The search focuses on events with a high transverse momentum system from initial-state-radiation jets recoiling against a potential sparticle system with significant missing transverse momentum. Events are categorized based on their lepton multiplicity, jet multiplicity, number of <c:math xmlns:c="http://www.w3.org/1998/Math/MathML" display="inline"> <c:mi>b</c:mi> </c:math> -tagged jets, and kinematic variables sensitive to the sparticle masses and mass splittings. The sensitivity extends to higher parent sparticle masses than previously probed at the LHC for production of pairs of electroweakinos, sleptons, and top squarks with mass spectra featuring small mass splittings (compressed mass spectra). The observed results demonstrate agreemen